(untitled) (LEARNing Landscapes, 2016)
The Great Lakes Stewardship Initiative (GLSI) has for 10 years been engaged in the systematic introduction of place-based learning approaches with an environmental and ecojustice focus throughout the state of Michigan. It has sought to create strong partnerships between schools and local organizations and agencies with the intent of cultivating knowledgeable and active citizen stewards. By the 2015-2016 academic year, the GLSI had worked with teachers in 283 schools, engaging over 80,000 students in its projects, demonstrating how place-based approaches can be brought to scale in both rural and urban communities.